KEBIJAKAN SERTIFIKASI (PROFESIONALISME) GURU DAN DOSEN - Fitrah Muthmainnah (Yayasan An-Nur Meunara Baro, 2026)
Professionalism of teachers and lecturers is a crucial factor in improving the quality of national education. Educators are required to have mastery of knowledge, skills, and professional attitudes to conduct effective teaching and learning. However, there are still gaps in the competencies and quality of educators, which affect the uneven distribution of educational quality. To address this issue, the Indonesian government has implemented a certification policy for teachers and lecturers as a form of competency recognition and an effort to enhance professionalism. This study aims to examine the teacher and lecturer certification policy, indicators of educator professionalism, and the impact of certification implementation on the quality of education. The method used is a literature review by analyzing various scientific sources, including journals, academic books, and official regulations. The findings indicate that certification aims to ensure educator competence, improve the quality of learning, and encourage continuous professional development. Educator professionalism is reflected in the mastery of knowledge, pedagogical and professional skills, and a mental attitude that upholds ethics and responsibility. Certification provides positive impacts, such as increased work motivation, educator performance, learning quality, and recognition of the teaching profession. Nevertheless, the implementation of certification also presents several challenges, including administrative burdens, discrepancies between policy objectives and implementation, and increased workload, which may reduce educators’ focus on teaching. Therefore, policy strengthening and improvements in certification implementation are needed to maximize its benefits and effectively contribute to enhancing educator professionalism and national education quality.